(untitled) (DARYAFT, 2022)
History of Urdu literature has been a very phenomenal subject of Urdu research. Our book-shelves are adorned and well equipped with esteemed writings of esteemed historians of Urdu language and literature. It is the subject of keen importance to analyze, compare, value and put them on the touch-stone of modern research that invites the critic to highlight the right areas where the historians have done exceedingly well and find genuine requisitions, still deemed necessary to revise the existing history works. Jameel Jalibi is the most famous and well-read historian of Urdu language and literature among the all. His (book series) “Tareekh-e-Adab-e-Urdu” consisting of 4 volumes keeps the place amongst highest ranks of history of Urdu. In this article, the technique of all of his four volumes has been discussed chronologically, critically and analytically. It has been studied in the liaison with modern trends and needs of research and criticism. The right amendments, displacements and additions, wherever are deemed mandatory to be done, in the historic study of Jameel Jalibi have been discussed. This article will offer the critics and researchers to revise the standards of historic mode of research and put the rational approach of research in literary works